2022
DOI: 10.1186/s13034-022-00491-w
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent mental health services in the Western Cape Province of South Africa: the perspectives of service providers

Abstract: Background Current work in the field point to the need to strengthen child and adolescent mental health services (CAMHS) globally, and especially in low- and middle-income countries (LMICs). Policy development, planning and service provision must be relevant to the needs of stakeholders at grassroots level, and should include their perspectives. This study set out to explore the perspectives and lived experiences of service providers, including their recommendations to strengthen CAMHS in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our "Discover" phase also highlighted potential implementation approaches to overcome barriers to mental health service integration within PrEP delivery for South African AGYW. Recent qualitative work with South African primary providers reported a similar set of potential implementation strategies to promote mental health services in primary care, including community outreach, staff supervision, flexible service delivery models, and screening and referral mechanisms [51,52]. Studies to adapt the Friendship Bench in Botswana, Vietnam and Malawi have all reported challenges with training and supervising younger lay counsellors, intervention fidelity, loss to follow-up and community stigma, underscoring the importance and relevance of the implementation approaches identified in our research [35,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Our "Discover" phase also highlighted potential implementation approaches to overcome barriers to mental health service integration within PrEP delivery for South African AGYW. Recent qualitative work with South African primary providers reported a similar set of potential implementation strategies to promote mental health services in primary care, including community outreach, staff supervision, flexible service delivery models, and screening and referral mechanisms [51,52]. Studies to adapt the Friendship Bench in Botswana, Vietnam and Malawi have all reported challenges with training and supervising younger lay counsellors, intervention fidelity, loss to follow-up and community stigma, underscoring the importance and relevance of the implementation approaches identified in our research [35,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The experiences of responsive and person-centred care were recognised and appreciated by the users. In an earlier publication, service providers shared some of their innovations to provide acceptable CAMHS in facilities despite the challenges mentioned (11). Here, the success of service innovations was re ected in the voices of the users.…”
Section: Create Separate Services For Child and Adolescent Mental Healthmentioning
confidence: 99%
“…Over the last few years, we have been evaluating the CAMH landscape of services and needs in the Western Cape, one of the nine South African provinces. Findings to date have identi ed a lack of policy and implementation at the level of the policy landscape, high resource limitations (9) and signi cant challenges as perceived by senior stakeholders (10) and grassroots service providers (11). One of the key 'landscapes' not previously examined in the South African context is the perspective of service users.…”
mentioning
confidence: 99%